The Recovery Umbrella in the World of Elite Sport: Do Not Forget the Coaching and Performance Staff - Julio Calleja-González; Stephen P. Bird; Thomas Huyghe; Igor Jukic; Francesco Cuzzolin; Francesc Cos; Diego Marqués-Jiménez; Luka Milanovic; Jaime Sampaio; Isaac López-Laval; Sergej M. Ostojic; Margaret T. Jones; et al. (MDPI AG, 2021)
In the field of sports science, the recovery umbrella is a trending topic, and even more so in the world of elite sports. This is evidenced by the significant increase in scientific publications during the last 10 years as teams look to find a competitive edge. Recovery is recognized to be an integral component to assist athlete preparation in the restoration of physical and psychological function, and subsequently, performance in elite team sports athletes. However, the importance of recovery in team staff members (sports coaches and performance staff) in elite sports appears to be a forgotten element. Given the unrelenting intense nature of daily tasks and responsibilities of team staff members, the elite sports environment can predispose coaches to increased susceptibility to psycho-socio physiological fatigue burden, and negatively affect health, wellbeing, and performance. Therefore, the aim of this opinion was to (1) develop an educational recovery resource for team staff members, (2) identify organizational task-specific fatigue indicators and barriers to recovery and self-care in team staff members, and (3) present recovery implementation strategies to assist team staff members in meeting their organizational functions. It is essential that we do not forget the coaching and performance staff in the recovery process.